The Effect of Competence and Professionalism on Employee Performance Through the Mediation of Information Technology Proficiency at BMKG Regional Office III - I Kadek Oca Santika; I Nengah Suardhika; Gregorius Paulus Tahu (International Journal of Economics and Management Sciences, 2025)
Human resources are a crucial asset for organizations, as their competence and professionalism greatly influence employee performance and the achievement of organizational objectives. At the MKG Office of Region III, several performance issues have been identified, including skill mismatches, high absenteeism rates as an indicator of low professionalism, and limited adaptability to information technology systems. These challenges underscore the need for strategic human resource development. This study aims to analyze the impact of competence and professionalism on employee performance, with information technology mastery serving as a mediating variable. A quantitative research approach was applied, involving all 115 employees as respondents through questionnaires, interviews, and documentation. Path analysis was used to evaluate the relationships between the variables. The findings reveal that both competence and professionalism have a positive and significant influence on employee performance. Furthermore, these variables also positively affect information technology mastery, which in turn significantly improves performance. The analysis demonstrates that information technology mastery mediates the relationship between competence and professionalism with employee performance, indicating the importance of digital skills in modern workplaces. In conclusion, enhancing competence and professionalism, alongside strengthening information technology mastery, is essential for improving employee performance at the MKG Office of Region III. The study recommends implementing strategic human resource programs that focus on digital proficiency to support organizational effectiveness and adaptability in the digital era.